2004
DOI: 10.1007/s00595-003-2736-7
|View full text |Cite
|
Sign up to set email alerts
|

Jugular Venous Oxygen Saturation During Mild Hypothermic Versus Normothermic Cardiopulmonary Bypass in Elderly Patients

Abstract: The SjvO(2) value was better during mild hypothermic CPB than during normothermic CPB in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Hemodynamic parameters and arterial and jugular venous blood gases were measured at different times, as previously described in detail [15]. The presence or absence of carotid artery stenosis, defi ned as narrowing of greater than 50% [16], was confi rmed by preoperative ultrasonography and MRI.…”
Section: Operative Proceduresmentioning
confidence: 99%
“…Hemodynamic parameters and arterial and jugular venous blood gases were measured at different times, as previously described in detail [15]. The presence or absence of carotid artery stenosis, defi ned as narrowing of greater than 50% [16], was confi rmed by preoperative ultrasonography and MRI.…”
Section: Operative Proceduresmentioning
confidence: 99%
“…[1][2][3][4] Thourani et al 2 reported the incidence of the perioperative neurological complications to be more frequent in diabetic patients than in patients without diabetes. However, the precise mechanisms of postoperative cognitive dysfunction in diabetic patients after cardiac surgery are still not fully understood.…”
Section: Introductionmentioning
confidence: 98%
“…However, the precise mechanisms of postoperative cognitive dysfunction in diabetic patients after cardiac surgery are still not fully understood. [1][2][3][4] The possible mechanisms of postoperative cognitive dysfunction are cerebral ischemia or cerebral desaturation due to hypoperfusion during cardiopulmonary bypass (CPB). 1,5,6 Croughwell et al 6 reported that lower values for internal jugular venous oxygen hemoglobin saturation (SjvO 2 ) at the end of rewarming were associated with cognitive deficits at 4-8 days after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Several studies have attempted to identify the preoperative or intraoperative predictors of cognitive change after CPB. [2][3][4][5][6][7][8][9] While atherosclerosis in the ascending aorta is a well-known risk factor for stroke after cardiac surgery, studies describing the relationship of atherosclerosis in the ascending aorta to postoperative cognitive dysfunction have generated conflicting results. [6][7]9 Furthermore, risk factors may vary by race or geographical location.…”
Section: Introductionmentioning
confidence: 99%